Comparing experimental and field‐measured traits and their variability in Central European grassland species. (13th April 2020) - Dostál, Petr; Fischer, Markus; Prati, Daniel
Abstract: Questions: What are the relative effects of intra‐ and interspecific differences on variation in five functional traits measured in a garden pot experiment? Are species rankings based on trait means and intraspecific trait variability (ITV) stable across the garden experiment and field measurements? Location: Experimental garden and two grassland systems in Central Europe. Methods: We measured five functional traits (plant height, leaf dry matter content [LDMC], leaf greenness, leaf thickness and specific leaf area SLA]) in 105 grassland species grown in a garden experiment subjected to fertilization, shading and waterlogging, complemented by a control. We also measured plant height, LDMC and SLA across grasslands in Germany, and used published values of the same traits from a field study in the Czech Republic. We then correlated speciesʼ trait means from different treatments in the experiment. We also compared garden‐ and field‐measured trait means and ITV in SLA, LDMC and plant height. Results: Most variation in the experiment‐measured trait data was explained by interspecific differences, except for leaf greenness (where species explained less than 50% of the variance), and the treatments had little effect on close associations of trait means. Species rankings based on SLA and LDMC, but not plant height, were stable across garden and field measurements. Though garden and field‐measured ITV were positively associated with each other, the associations were not significant. Conclusions: Our study indicates that species can be stably ranked based on SLA and LDMC means across different datasets (experimental and field‐based). To what extent species vary in their functional traits under field conditions can be, however, less well predicted from experimentally measured ITV. Garden‐measured differences in ITV should be thus used with caution when associated with species' performance and distribution patterns explored in the field. Abstract : We investigated whether species hierarchy based on mean trait values is conserved across experimental and field measurements. We also explored whether species with high intraspecific trait variability (ITV) in the experiment will also be variable under field conditions. Species hierarchy was conserved in case of mean trait values. Experimental and field‐measured ITV were positively, though non‐significantly associated with each other.